Scientific Goals of the Kunlun Infrared Sky Survey (KISS). (19th September 2016) - Burton, Michael G.; Zheng, Jessica; Mould, Jeremy; Cooke, Jeff; Ireland, Michael; Uddin, Syed Ashraf; Zhang, Hui; Yuan, Xiangyan; Lawrence, Jon; Ashley, Michael C. B.; Wu, Xuefeng; Curtin, Chris; et al.
Abstract: The high Antarctic plateau provides exceptional conditions for infrared observations on account of the cold, dry and stable atmosphere above the ice surface. This paper describes the scientific goals behind the first program to examine the time-varying universe in the infrared from Antarctica — the Kunlun Infrared Sky Survey (KISS). This will employ a 50cm telescope to monitor the southern skies in the 2.4μm K dark window from China's Kunlun station at Dome A, on the summit of the Antarctic plateau, through the uninterrupted 4-month period of winter darkness. An earlier paper discussed optimisation of the K dark filter for sensitivity (Li et al.2016 ). This paper examines the scientific program for KISS. We calculate the sensitivity of the camera for the extrema of observing conditions that will be encountered. We present the parameters for sample surveys that could then be carried out for a range of cadences and sensitivities. We then discuss several science programs that could be conducted with these capabilities, involving star formation, brown dwarfs and hot Jupiters, exoplanets around M dwarfs, the terminal phases of stellar evolution, fast transients, embedded supernova searches, reverberation mapping of AGN, gamma ray bursts and the detection of the cosmic infrared background.